2021
DOI: 10.1021/acs.jpcb.0c10865
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Malonamide Aggregation Deduced from Molecular Dynamics Simulations

Abstract: The aggregation of malonamide extractants diluted in an aliphatic solvent phase has been studied in the presence of water by molecular dynamics simulation. Using association criteria based on distances between molecules and graphs theory, the aggregate distribution has been computed and the corresponding Gibbs energy of aggregates and mass action law constants have been determined. Finally, a model allowing us to the compute critical micelle concentration and osmotic data for a variable concentration of extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…In order to probe the size of polar and apolar microdomains in [EBPip + ]­[NTf 2 – ] and [EOPip + ]­[NTf 2 – ] and compare them to those obtained in imidazolium-based ILs, we used the statistical tool introduced in the study of Shimizu et al which gives the average domain size by where P ( N a ) is the probability of finding an atom in a domain of size N a , SN a is the domain number of size N a , n F is the total frame number used in the computation, and n tot is the total atom number. The aggregates’ distribution as a function of their size S N a was obtained from the graph theory as the one developed in the study of Vatin et al For the polar domain, the C ring and A mid CoMs were chosen to define the aggregation with a minimum distance of 8.8 Å, that is, the minimum of the g ( r ) first peak (Figure S5). As in the study of Shimizu et al, we demonstrated that the polar network is continuous regardless of the size of the cation carbon tail.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In order to probe the size of polar and apolar microdomains in [EBPip + ]­[NTf 2 – ] and [EOPip + ]­[NTf 2 – ] and compare them to those obtained in imidazolium-based ILs, we used the statistical tool introduced in the study of Shimizu et al which gives the average domain size by where P ( N a ) is the probability of finding an atom in a domain of size N a , SN a is the domain number of size N a , n F is the total frame number used in the computation, and n tot is the total atom number. The aggregates’ distribution as a function of their size S N a was obtained from the graph theory as the one developed in the study of Vatin et al For the polar domain, the C ring and A mid CoMs were chosen to define the aggregation with a minimum distance of 8.8 Å, that is, the minimum of the g ( r ) first peak (Figure S5). As in the study of Shimizu et al, we demonstrated that the polar network is continuous regardless of the size of the cation carbon tail.…”
Section: Results and Discussionmentioning
confidence: 99%
“…At high concentration, polar regions of DMDBPMA head groups and nonpolar regions of aliphatic tails and solvent are interspersed in a bicontinuous-like fashion. Malonamide self-association is quantified by cluster analysis, an intuitive description of amphiphile aggregation that is accessible from simulation trajectories, , as described in the Supporting Information. Cluster size distributions are plotted in Figure .…”
mentioning
confidence: 99%
“…A connection between the Ornstein–Zernike correlation length and simulation clustering is desirable: it would link the former, an experimentally observable feature of interest, to the latter, a physically intuitive description of solution structure that is commonly applied to quantify extractant aggregation. ,, To that end, we compute a cluster correlation length, ξ cluster , from the malonamide clusters to qualitatively compare with ξ O‑Z . Here, ξ cluster is defined for N total molecules by where r ij is the distance between molecules i and j with δ ij being unity if the molecules are on the same cluster and zero otherwise .…”
mentioning
confidence: 99%
“…In order to simulate biological phenomena, molecular dynamics simulation methods provided more reliable results. 67–69 Here, all simulations were done using the NAMD-2.12 package 70 with the force field of CHARMM-36. 71 The VMD 72 program was also used for visualization and graphical analyses.…”
Section: Computational Detailsmentioning
confidence: 99%